Relationship between power and isometric strength with the repeat sprint ability in male professional soccer players - Vidal Maturana, Francisco; Gajardo Cid, Noé; Merino-Muñoz, Pablo; Hermosilla-Palma, Felipe; Valdés-Badilla, Pablo; Herrera-Valenzuela, Tomás (SPORT TK-EuroAmerican Journal of Sport Sciences, 2024)
The aim of this study was to relate variables of countermovement jump (CMJ) and isometric mid-thigh pull (IMTP) with the performance of the repeat sprint ability (RSA) in professional soccer players, as well as to determine the differences in CMJ and IMTP results according to the RSA performance. 54 professional soccer players were evaluated (mean age= 23.1 ± 5.1 years) in which the correlations were analyzed through Pearson´s coefficient. Subsequently, the group was divided into above (SM; N=27) and below (BM; N= 27) the median according to RSA performance in three variables and the student´s t-test for independent samples was used. Significant (p ≤ 0.05) low to moderate correlations (r= -0.27; -0.30; -0.31; 0.46 y 0.42) were obtained in IMTP and CMJ variables with the RSA. Significant difference (p ≤ 0.05) from moderate to large in favor of SM were found in variables of power, contact time and peak relative force and significant differences (p ≤ 0.05) from moderate to large in peak force and dynamic strength index in favor of BM. In conclusion, there is a relationship between power variables and relative isometric strength with RSA performance in professional soccer players.